2019
DOI: 10.1159/000496400
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>IL1RN</i></b> Polymorphisms Are Associated with a Decreased Risk of Esophageal Cancer Susceptibility in a Chinese Population

Abstract: Background: Recent evidence suggested that IL1RN (interleukin-1 receptor antagonist) polymorphisms increased the susceptibility to cancers. The present study aimed to evaluate whether IL1RN was related to esophageal cancer susceptibility in a Northwest Han Chinese population. Methods: The case-control study was conducted on 384 esophageal cancer patients and 499 healthy controls. We successfully genotyped four SNPs distributed in IL1RN. The Gene Expression Profiling Interactive Analysis (GEPIA) database was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, a pooled analysis of three studies showed that IL1RN rs2637988 was correlated with an increased risk of NHL 22 , probably by increasing predisposition to shorter immune responses 23 . Conversely, several other polymorphisms in IL-1RN (rs3181052, rs452204 and rs315919) are associated with a decreased risk of esophageal cancer in a Northwest Han Chinese population 11 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, a pooled analysis of three studies showed that IL1RN rs2637988 was correlated with an increased risk of NHL 22 , probably by increasing predisposition to shorter immune responses 23 . Conversely, several other polymorphisms in IL-1RN (rs3181052, rs452204 and rs315919) are associated with a decreased risk of esophageal cancer in a Northwest Han Chinese population 11 .…”
Section: Discussionmentioning
confidence: 94%
“…IL-1 is a key inflammatory cytokine that has been shown to induce tumor growth, angiogenesis, invasiveness and metastasis in various cancers 24 . IL-1RN can alter IL-1 expression levels and compete for binding spots on the IL-1 receptors, consequently modulating the effectiveness of IL-1 signaling and IL-1 related immune and inflammatory responses 11 . Despite the convincing results, our study has several limitations, which include the analysis of a relatively small sample size and the gene environmental interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL1RN encodes a member of the interleukin-1 (IL-1) cytokine family and is related to cytokine signaling in the immune system and the IL-1 signaling pathway. 26 CXCL10 encodes a chemokine of the CXC subfamily and ligand for the receptor CXCR3. Binding of this protein to CXCR3 results in pleiotropic effects, including stimulation of monocytes, natural killer cell and T cell migration, and modulation of adhesion molecule expression.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al found that IL1RN rs315919, rs452204 and rs3181052 polymorphisms were associated with a decreased risk of esophageal cancer in a Northwest Han Chinese population. 32 Niedźwiecki et al suggested that interleukin-1 receptor antagonist (IL-1ra) might have a critical role in the development of anaplastic thyroid carcinoma and follicular thyroid carcinoma. 33 As a chemokine, platelet factor 4 (PF4, CXCL4) is involved in the pathogenesis of autoimmune thyroid diseases.…”
Section: Discussionmentioning
confidence: 99%